Spatial effect of ethnicity on cross-border regions. Comparative analysis for a cultural aspect based on territorial and network perspectives: the cases of the EU Basque and Upper Rhine border regions - Bakry, Ahmed; Growe, Anna (European planning studies, 2024)
Cultural proximities are significant aspects that can foster or hinder integration in border regions; however, culture is underrepresented in border studies. Such cultural proximities are affected by cultural characteristics and different types of socio-cultural regional constructs, such as gesellschaft (civic societies) and gemeinschaft (ethnic communities). These characteristics influence both the level of the cultural border networks and the degree of cultural territorial clustering. This study is concerned with answering these questions: How can culture - from the territorial and network perspectives - be measured in two different EU cross-border contexts? How does ethnicity and different socio-cultural constructs in cross-border regions influence spatio-cultural networks and clusters? What different cross-border cultural network typologies exist? What different cultural city types can be differentiated? The first case is the Basque region which tends to symbolise a gemeinschaft ethnic region and the second is the Upper Rhine gesellschaft region. The study is based on quantitative and qualitative datasets. It is argued that the existence of ethnic attributes in European cross-border regions supports internal cultural integration across the border, whereas the cultural networks in non-ethnic regions reach out relatively more to other parts of the EU, implying external integration capabilities.
Gesehen am 15.02.2024